Use of palliative chemotherapy in South Africa: National survey of paediatric oncologists and experience in a single unit - Büchner, Ané (University of Cape Town, 2020)
BACKGROUND: Palliative chemotherapy is cancer-directed therapy, which aims at stopping or slowing down the progression of the malignancy even though it may not have any potential for remission or cure. In South Africa, delayed diagnosis of childhood cancer is a common problem for a variety of reasons including lack of health care facilities, transport, information about the disease and delayed presentation due to traditional healer visits or other cultural issues. In patients who present with advanced cancer, or in patients with relapsed cancer without realistic hope of cure, palliative chemotherapy can be offered in an attempt to manage symptoms, improve quality of life and prolong meaningful survival. OBJECTIVES: This research study evaluated South African paediatric oncologists' perspectives and practices regarding the use of chemotherapy in patients with cancer with no realistic hope of cure. The second part of the study described the use of palliative chemotherapy in patients who received treatment at the Steve Biko Academic Hospital Paediatric oncology unit. DESIGN & METHOD: An online survey was conducted among paediatric oncologists in South Africa. The main aims of the questionnaire were to assess paediatric oncologists' considerations around the use of palliative chemotherapy, and then focus on the most recent patients treated with palliative chemotherapy. For the second part of the study, a file review was done of deceased patients who died in the period from January 2012 to December 2018 and who had received palliative chemotherapy as part of their cancer management. We reviewed diagnoses, palliative chemotherapy regimens, timing of initiation and stopping palliative chemotherapy, and whether end of life decisions and discussions were documented. RESULTS: A total of 41 participants completed the survey, giving a response rate of 89%. The majority of the paediatric oncologists were either neutral or agreed that palliative chemotherapy should be considered. The most important treatment aim was to improve quality of life of the patient (92.7% of respondents). The most important considerations when prescribing palliative chemotherapy was to minimise toxicity of the chemotherapy regimen (4.56 mean, SD=0.5 utilising a 5 point scale where 1=not important to 5=very important), and the effectiveness of the chemotherapy (4.37; SD=0.48). Only 19.5% of patients received treatment primarily because parents requested it. According to the oncologists polled, the key considerations were largely achieved in the most recent patient treated with palliative chemotherapy. Individual opinions and preferences concerning recommending palliative chemotherapy differ between paediatric oncologists. Of the 305 patient deaths recorded in the study period, a total of 74 patients had received palliative chemotherapy and were included in the file review. The most common diagnoses were neuroblastoma (18.2%), retinoblastoma (15.6%) and osteosarcoma (14.3%). At the time of diagnosis, the median age of the patients was 6.0 years (range 0.3 to 17.6 years). In 47 patients (63.5%) the disease was deemed incurable at first diagnosis and palliative chemotherapy given from the onset of treatment, while 27 patients (36.5%) were given palliative chemotherapy at relapse. The median time from last palliative chemotherapy to death was 30 days (range 0-742 days). The main documented aim of palliative chemotherapy was to improve symptom control (97.3%) while parents' opinion played an important role in 32.9% of cases. About half of the patients (41 of 74, 55.4%) had documentation of symptomatic improvement. CONCLUSION: Although the overall attitude towards the use of palliative chemotherapy is positive, there is great inter-individual variation between oncologists in opinions and experience. The lack of empirical data to justify recommendations about palliative chemotherapy remains a problem, and the researcher hopes that this study will spark productive discussion and planning towards more structured use of palliative chemotherapy in children with cancer in South Africa. This study shows that many decisions around end of life care and decision-making could be better researched using a quantitative, prospective, interview-based approach. Repeated measurements of the child and family's quality of life and its associations with palliative chemotherapy should be a research priority in future.